2022
DOI: 10.3389/fcvm.2022.789331
|View full text |Cite
|
Sign up to set email alerts
|

SS31 Ameliorates Oxidative Stress via the Restoration of Autophagic Flux to Protect Aged Mice From Hind Limb Ischemia

Abstract: BackgroundOxidative stress and impaired autophagic flux play important roles in the development of peripheral artery disease (PAD). SS31 is considered an important antioxidant peptide and autophagy regulator. We aimed to investigate the role of SS31 in PAD myopathy and its possible mechanism both in vivo and in vitro.MethodsA hind limb ischemia (HLI) model was established with old C57BL/6 (14-month-old) mice. Mice in the SS31 group were intraperitoneally injected with SS31 (3 mg/kg) for 4 weeks. We examined sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Further, Rui et al indicated that under hypoxic conditions, autophagy plays a negative role in muscle differentiation, and the inhibition of autophagy promotes cell survival and protects against myotube degradation [ 29 ]. However, Yang et al showed that restoring autophagic flux protects skeletal muscles from oxidative stress in old C57BL/6 (14-month-old) mice [ 30 ]. Zhang et al suggested that the myogenic differentiation of C2C12 myoblasts decreased under hypoxia for 7 days, which may be due to the inhibition of autophagy activity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, Rui et al indicated that under hypoxic conditions, autophagy plays a negative role in muscle differentiation, and the inhibition of autophagy promotes cell survival and protects against myotube degradation [ 29 ]. However, Yang et al showed that restoring autophagic flux protects skeletal muscles from oxidative stress in old C57BL/6 (14-month-old) mice [ 30 ]. Zhang et al suggested that the myogenic differentiation of C2C12 myoblasts decreased under hypoxia for 7 days, which may be due to the inhibition of autophagy activity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%